Implementasi Know Your Customer (KYC) sebagai Upaya Pencegahan Tindak Pencucian Uang di Industri Perbankan Indonesia - Ginanjar Hasanudin; Jajang Nurjaman; Dadang Husen Sobana (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
The application of the Know Your Customer (KYC) principles in the Indonesian banking sector plays a crucial role in preventing money laundering activities. KYC, which includes data collection, identity verification, transaction monitoring, and risk management, helps detect illegal activities as well as ensuring compliance with applicable regulations. This study aims to analyze the implementation of KYC as a measure for preventing money laundering in Indonesia and to evaluate the effectiveness of procedures applied by financial institutions. The research method used is a qualitative approach with a descriptive design through a literature review, which gathers and analyzes various written sources related to KYC and money laundering prevention. The findings of the study indicate that the implementation of KYC in Indonesia's banking sector is highly effective in detecting illegal activities and preventing money laundering. The money laundering case involving Rafael Alun Trisambodo illustrates how KYC procedures, such as transaction monitoring and careful data analysis, successfully uncovered money laundering practices and led to the prosecution of the perpetrators. With consistent and strict implementation of KYC, the banking sector can maintain the integrity of the financial system and prevent harmful abuses.